Issues, Concepts and Applications for Sustainability (Glocalism: Journal of Culture, Politics and Innovation, 2018)
Humanity and societies today face important challenges related to sustainability and these are expected to become more significant in the future. Making societies and their development more sustainable requires the consideration of economic, social, environmental and other factors. Sustainability assessment tools are needed to evaluate how is the sustainability of a process or system, and how that is affected when a change is made. To account for all relevant factors, a comprehensive set of indicators is required, including both quantitative indicators which are measurable and practical and qualitative indicators where necessary. In this article, sustainability concepts and definitions are reviewed and the historical context for sustainability is briefly described. Then sustainability is discussed, focusing on its economic, environmental and social dimensions, and the related concept of sustainable development is examined. Issues related to sustainability are discussed throughout. Finally, assessment measures for sustainability are examined, and several applications are presented.
Keywords: sustainability; sustainable development; environment; climate change; equity